Development of a potential LPG sensor based on a PANI–Co3O4 nanocomposite that functions at room temperature. (28th October 2019) - Singh, Neetu; Singh, Prabhat Kumar; Singh, Mridula; Gangopadhyay, Debraj; Singh, Saurabh Kumar; Tandon, Poonam
Abstract : Nanostructured Co3 O4 was synthesized by a sol–gel technique while 30% & 40% Co3 O4 –PANI (polyaniline) nanocomposites were successfully prepared employing an in situ polymerization technique. Abstract : Nanostructured Co3 O4 was synthesized by a sol–gel technique while 30% & 40% Co3 O4 –PANI (polyaniline) nanocomposites were successfully prepared employing an in situ polymerization technique. Various characterization techniques were utilized to examine the structural, spectroscopic, topographical, elemental and chemical features of the nanostructured Co3 O4 and Co3 O4 –PANI nanocomposites utilizing XRD, FTIR, SEM and EDX respectively. The crystallite sizes of Co3 O4, 30% Co3 O4 –PANI and 40% Co3 O4 –PANI were calculated, with the aid of XRD patterns, to be 41, 30 and 22 nm, respectively. By scrutinizing the SEM results of all the materials, a nearly spherical morphology was perceived. Numerous pores were also observed in their surface morphology which shows that the prepared materials are highly advantageous for gas sensing. Further, the materials were utilized for LPG sensing. Significant parameters of LPG sensing such as response time, recovery time, sensitivity and reproducibility were calculated for both materials. LPG sensing studies indicate that the 40% Co3 O4 –PANI nanocomposite, which exhibits lower response and recovery times, i.e. 10 s and 32 s, might be an efficient and potential material for use as an LPG sensor.